Year-End Newsletter of the CGIAR Science Program on Food Frontiers and Security - Awinoh, Martha; Okello, Anna; Hollerich, Gillian; Carrillo, Lucia; Ibukun, Taiwo; Victor, Andin; Hanke-Louw, Nora (CGIAR Science Program on Food Frontiers and Security, 2025)
The world is facing growing uncertainty from climate extremes to displacement and fragile governance. Yet within these challenges, one truth is clear: food systems on the frontlines must become stronger, safer, and more inclusive. The year 2025 reminded us of the power of concerted efforts when science, policy actors, and communities work together to protect lives, restore stability, and build resilience in the most vulnerable places.